Concept and Dimensions of Web 4.0 - Almeida, Fernando Luis (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Web 4.0 is a new evolution of the Web paradigm based on multiple models, technologies and social relationships. The concept of Web 4.0 is not totally clear and unanimous in literature, because it is composed by several dimensions. In this sense, this study uses a systematic review approach to clarify the concept of Web 4.0 and explore its various dimensions, analyzing if they have elements in common. The findings indicate that the number of studies published from 2009 to 2017 on this field significantly increased, having reached a peak in 2014. Furthermore, we identified five dimensions associated with the Web 4.0 paradigm, in which the terms â€œpervasive computingâ€ and â€œubiquitous computingâ€ are the most widely used in the literature. On the other side, terms such as â€œWeb 4.0â€, â€œsymbiotic Webâ€ and â€œWeb social computingâ€ are not often used.